Myotonia Congenita in Australian Merino Sheep with a Missense Variant in CLCN1 - Leah K. Manning; Katie L. M. Eager; Cali E. Willet; Shaun Slattery; Justine H. McNally; Zoe B. Spiers; Mark Hazelton; Georgina Child; Rick Duggan; Brendon A. O’Rourke; Imke Tammen (Animals, 2024)
Myotonia congenita is a hereditary, non-dystrophic skeletal muscle disorder associated with muscle stiffness due to delayed muscle relaxation after contraction. We review myotonia congenita in domesticated animals and humans and investigated suspected myotonia congenita in a flock of Merino sheep in Australia. In 2020, a property in New South Wales reported a four-year history of lambs that would fall on disturbance before rapidly recovering, with 13 affected sheep identified in 2020. Episodes were associated with a short period of tetanic spasms and a stiff gait upon rising. Lambs were otherwise normal between episodes, although over time, lost body condition and occasionally died from misadventure. An inherited condition was considered from limited pedigree information and a preliminary diagnosis of myotonia congenita was made based on clinical presentation. Biochemistry from four sheep found variable, but typically mild increases in creatine kinase (CK) and aspartate aminotransferase (AST). Modified electromyography on six affected sheep found irregular electrical activity within the muscle. For four sheep, there were no consistent significant abnormalities on post mortem examination and histopathology—typical for this condition. A review of the Online Mendelian Inheritance in Man (OMIM) and Online Mendelian Inheritance in Animals (OMIA) databases was conducted to summarise information about myotonia congenita in humans and eight non-human species of animals. Comparing the characteristic clinical presentation, pathology and electromyography data of affected Merino sheep to similar conditions in other species assisted the identification of likely candidate genes. Whole genome sequencing of two affected lambs detected a missense variant in CLCN1 (NC_056057.1:g.107930611C>T; XM_004008136.5:c.844C>T; XP_004008185.4:p.(P282S)), with a predicted deleterious effect on protein function. An SNP genotyping assay was developed, and the variant segregated with the disease in 12 affected sheep and obligate carrier rams under an assumed recessive mode of inheritance. Identifying a likely causal variant and developing a diagnostic test allows screening of suspected affected or carrier Merino sheep for early intervention to reduce propagation of the variant within flocks.